Crisis And Ambivalent Futures in Middle English Romance. (3rd July 2022) - Sanok, Catherine
ABSTRACT: This paper seeks to contribute to recent work that explores the relationship between affect and temporality by looking at the relationship between crisis, ambivalence, and futurity. The cluster's operative definition of crisis, highlighting its early use to indicate a turning point in the progress of a disease, already links crisis to possible alternative futures: unlike a catastrophe — an event that is disastrous, irreversible, and final — a crisis is in process, its course and outcome undetermined. Or rather a crisis is experienced as such: although it's not usually defined in this way, crisis is necessarily as much an affective category as an ontological one, a situation that allows for feeling fear and hope, and an experience of being oriented to the world by both terror and possibility. Borrowing from recent feminist and queer reconceptualizations of ambivalence to understand its bearing on experiences of crisis, this essay explores ambivalence in two Middle English romances — namely Amis' ambivalence about the sacrificial killing of his children in Amis and Amiloun and Criseyde's ambivalence about returning to Troy in Troilus and Criseyde — to explore its implications for medieval models of futurity.